Salivary protein kinase C alpha and novel microRNAs as diagnostic and therapeutic resistance markers for oral squamous cell carcinoma in Indian cohorts - Saproo, Sheetanshu; Sarkar, Shashanka S.; Gautam, Vishakha; Konyak, Chingmei W.; Dass, Gouri; Karmakar, Arpita; Sharma, Mansi; Ahuja, Gaurav; Gupta, Anand; Tayal, Juhi; Mehta, Anurag; Naidu, Srivatsava (Frontiers in Molecular Biosciences, 2023)
Oral squamous cell carcinoma (OSCC) is the second leading cause of cancer-related morbidity and mortality in India. Tobacco, alcohol, poor oral hygiene, and socio-economic factors remain causative for this high prevalence. Identification of non-invasive diagnostic markers tailored for Indian population can facilitate mass screening to reduce overall disease burden. Saliva offers non-invasive sampling and hosts a plethora of markers for OSCC diagnosis. Here, to capture the OSCC-specific salivary RNA markers suitable for Indian population, we performed RNA-sequencing of saliva from OSCC patients (n = 9) and normal controls (n = 5). Differential gene expression analysis detected an array of salivary RNAs including mRNAs, long non-coding RNAs, transfer-RNAs, and microRNAs specific to OSCC. Computational analysis and functional predictions identified protein kinase c alpha (PRKCA), miR-6087, miR-449b-5p, miR-3656, miR-326, miR-146b-5p and miR-497-5p as potential salivary indicators of OSCC. Notably, higher expression of PRKCA, miR-6087 and miR-449b-5p were found to be associated with therapeutic resistance and poor survival, indicating their prognostic potential. In addition, sequencing reads that did not map to the human genome, showed alignments with microbial reference genomes. Metagenomic and statistical analysis of these microbial reads revealed a remarkable microbial dysbiosis between OSCC patients and normal controls. Moreover, the differentially abundant microbial taxa showed a significant association with tumor promoting pathways including inflammation and oxidative stress. Summarily, we provide an integrated landscape of OSCC-specific salivary RNAs relevant to Indian population which can be instrumental in devising non-invasive diagnostics for OSCC.